ANALISIS KUALITAS SISTEM INFORMASI HOTEL OYO DI KOTA BATAM MENGGUNAKAN METODE WEBQUAL 4.0 - vallerin, anggie; Amrizal, Amrizal (Computer Science and Industrial Engineering, 2022)
Conditions of intense competition, especially in Batam and in the hospitality sector, there are several hotels in Batam that use a Web-based OYO information system. Where OYO collaborates with property owners who do not yet have a hotel management system, where OYO task is to control and develop hotel management then connect and market it through the OYO application to make it more accessible online. The technique used is by distributing questionnaires orally to respondents with 25 questions and a sample of 115 respondents.The use of the measuring instrument is 5 points Likert scale. Using descriptive analysis for data analysis methods, Using validity and reliability test for the data quality test, then there is a classical assumption test using normality and heteroscedasticity tests, and hypothesis test using T and F tests with help of statistical software SPSS 20. Based on the results that the variables of Usability, Information Quality, Interaction Quality all three have a positive influence and also have a significant influence on the Website Quality.